Unveiling the spectrum of sudden cardiac death: a multidisciplinary analysis from the Friuli Venezia Giulia registry - Radaelli, D.; Moreschi, C.; Bussani, R.; Basciu, M.; Di Loreto, C.; Concato, M.; Addobbati, R.; Franzin, M.; Cova, M. A.; Pagnan, L.; Girotto, G.; Lenarduzzi, S.; et al. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionSudden cardiac death in individuals aged ≤50 years represents a significant public health issue with diverse aetiologies and age-specific mortality patterns.Material and methodsThis study reports findings from the Friuli Venezia Giulia Sudden Cardiac Death Register in the Young (2021–2024), which employs a multidisciplinary approach integrating autopsy, post-mortem cardiac MRI, toxicology, and genetic testing to investigate sudden and unexpected deaths in the region.ResultsIn the first four years a total of 107 cases (mean age 40 ± 10 years; 78% male) were included in the register with ischemic heart disease as the leading cause of death (32%), followed by substance-related fatalities (25%) and sudden arrhythmic death syndrome (SADS, 11%). Substance-related deaths predominated in individuals ≤35 years, while ischemic heart disease was more frequent in those >35 years. Toxicological analyses revealed polysubstance use in most positive cases, with ethanol, benzodiazepines, and methadone most detected. Genetic testing was performed in 14 cases identified pathogenic or likely pathogenic variants in five individuals, mainly involving hypertrophic cardiomyopathy, highlighting the utility of molecular autopsy for familial risk assessment. The registry uncovered a higher burden of substance-related mortality than official statistics, emphasizing underreporting in death certificates. Post-mortem cardiac MRI contributed to detecting myocardial abnormalities, aiding pathological examination.DiscussionThe study underscores the importance of a comprehensive, multidisciplinary registry model for accurate SCD cause determination, improved family screening, and targeted prevention strategies. These findings provide valuable epidemiological and genetic insights relevant to public health interventions, particularly in regions with unique genetic backgrounds such as Friuli Venezia Giulia.